Effect of Sequential Inoculum of Beta-Glucosidase Positive and Probiotic Strains on Brine Fermentation to Obtain Low Salt Sicilian Table Olives - Pino, Alessandra; Vaccalluzzo, Amanda; Solieri, Lisa; Romeo, Flora V.; Todaro, Aldo; Caggia, Cinzia; Arroyo-López, Francisco Noé; Bautista-Gallego, Joaquin; Randazzo, Cinzia L. (Frontiers in Microbiology, 2019)
In the present study, the β-glucosidase positive strain Lactobacillus plantarum F3.3 was used as starter during the fermentation of Sicilian table olives (Nocellara Etnea cultivar) at different salt concentrations (5 and 8 %), in order to accelerate the debittering process. In addition, the potential probiotic Lactobacillus paracasei N24 strain was added after 60 days of fermentation with the aim to formulate a product with high functional value. Un-inoculated brine samples at 5 and 8% of salt were used as control. The fermentation was monitored till 120 days through physico-chemical and microbiological analyses. In addition, volatile organic compounds and sensorial analyses were performed during the process and at the end of the fermentation, respectively. Lactic acid bacteria and yeasts were, in depth, studied by molecular methods and the occurrence of the potential probiotic N24 strain in the final products was determined. Results highlighted that inoculated brines exhibited a higher acidification and debittering rate than control ones. In addition, inoculated brines at 5% of salt exhibited higher polyphenols (hydoxytyrosol, tyrosol, and verbascoside) content compared to samples at 8% of NaCl, suggesting a stronger oleuropeinolytic activity of the starter at low salt concentration. Lactobacilli and yeasts dominated during the fermentation process, with the highest occurrence of L. plantarum and Wickerhamomyces anomalus, respectively. In addition, a high survival rate of the promising probiotic L. paracasei N24 strain was confirmed in the final product. Hence, the sequential inoculum of beta-glucosidase positive and potential probiotic strains could be proposed as a suitable technology to produce functional low salt Sicilian table olives.